2020
DOI: 10.1002/jhet.3867
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and anticancer evaluation of acetamide and hydrazine analogues of pyrimidine

Abstract: A library of acetamide and hydrazine analogues were generated on the pyrimidine ring through a multistep reaction starting from 5‐nitro‐pyrimidine‐4,6‐diol and pyrimidine‐4,6‐diol, respectively. The synthesized analogues were screened for in vitro cytotoxic activity against various human cancer cell lines like HCT‐1 and HT‐15 (colon), MCF‐7(breast), PC‐3 (prostrate), SF268 (CNS) using MTT method. From the bioassay results, it was observed that even though many of the synthesized derivatives exhibited a good po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Therefore, special attention has also been given to acetamide medications because of their possible use as a therapeutic agent. Acetamide derivatives and their analogs representing a high potential of biological activities including anti-inflammatory [ 63 ], anti-oxidant [ 64 ], anti-cancer [ 65 ], anti-convulsant [ 66 ], anti-hypoxic and anti-microbial [ 67 ], antituberculosis agents [ 68 ] and anti-COVID-19 molecules [ 69 ]. In addition, several acetamide derivatives are used to improve some enzymes that inhibit HIV virus activity from replicating [ 70 ].…”
Section: An Overview Of Acetamide Derivatives As Possible Therapeuticmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, special attention has also been given to acetamide medications because of their possible use as a therapeutic agent. Acetamide derivatives and their analogs representing a high potential of biological activities including anti-inflammatory [ 63 ], anti-oxidant [ 64 ], anti-cancer [ 65 ], anti-convulsant [ 66 ], anti-hypoxic and anti-microbial [ 67 ], antituberculosis agents [ 68 ] and anti-COVID-19 molecules [ 69 ]. In addition, several acetamide derivatives are used to improve some enzymes that inhibit HIV virus activity from replicating [ 70 ].…”
Section: An Overview Of Acetamide Derivatives As Possible Therapeuticmentioning
confidence: 99%
“…Many chalcones also can be obtained via coupling reactions by using different reactants (63)(64)(65)(66)(67)(68)(69). Several reactions involved C-C and C-heteroatom covalent bond via oxidative addition transmetalation-reductive elimination, as illustrated in Scheme 12 [93].…”
Section: Introduction To Synthesis Of Chalcone and Its Derivativesmentioning
confidence: 99%
“… 17 In terms of medicine, roughly one-quarter of all marketed drugs (and two-thirds of all drug candidates) contain at least one amide bond. 18 Furthermore, molecules with an acetamide linkage or its derivatives as core structures have received significant attention due to their potential therapeutic applications as anti-inflammatory, 19 anticancer, 20 analgesic, 21 antimicrobial, 21 23 anticonvulsant, 24 antituberculosis agents, 25 and anti-COVID-19 agents. 26 Some acetamide derivatives, such as paracetamol V 27 ( Figure 1 ), have been shown to have analgesic or sedative properties.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was reported that molecules with an acetamide linkage or its derivatives have gotten much attention due to their potential therapeutic applications, including anticancer [3], analgesic [4,5], antimicrobial [6], anticonvulsant [7], antituberculosis agents [8], and anti-COVID-19 agents [9]. Furthermore, in recent decades, thiazole derivatives have received a lot of attention.…”
Section: Introductionmentioning
confidence: 99%